(untitled) (CAHIERS MAGELLANES-NS, 2024)
This paper Studied twenty-two (22) college libraries at Purba Bardhaman District, affiliated to the Burdwan University and try to find out the present status of ICT infrastructures and services in these college libraries. College is the first step in imparting higher education among the students. Library associated with the college plays an important role in teaching and learning process of students and faculty members. Therefore, it is very essential to pay enough attention for the development of these college libraries. This paper discussed various aspect of ICT application, infrastructure facilities, e-resource usage and services provided to the users. This paper also light throws on Different type of challenges and issues facing while implementing ICT in these college libraries. Study found that lack of human resources is common in almost all college. Negligence of higher authorities, lack of fund allocation, proper ICT implementation policy and ICT trained staffs are important issues facing by the colleges.